A Novel THz Photoconductive Source and Waveguide Based on One-dimensional Nano-grating - Jafarlou, Saman (University of Waterloo, 2013)
A terahertz photoconductive source structure with nano-grating electrodes is proposed. The resonance modes of the one-dimensional nano-grating and their affect the optical power absorption are studied. In addition, an approach for optimal design of the grating to maximize the photocurrent for different proposed DC biases, is presented. The dependence of the photocurrent on physical parameters of photomixer are analyzed. A fast analysis method for a new terahertz waveguide for photo-mixing is proposed. The wave-guiding mixer structure is a modified parallel plate waveguide (PPWG) in which the top plate is replaced by a periodic array of sub-wavelength nano-slits. The substrate of the PPWG is made of a fast photoconductive material in which laser photomixing/absorption occurs. The characteristic equation of the modified PPWG when used as a THz waveguide is derived analytically, and its guided modes are studied in details over THz range of frequencies. The accuracy of the analytical results are verified by comparison with full-wave numerical simulations. The criteria for choosing the suitable mode for photomixing application are also discussed. Finally, based on dyadic Green’s function representation, a systematic approach is provided for calculating the amplitude of the guided modes that are excited by an arbitrary photocurrent.
Keywords: terahertz; photomixer; Plasmonic; Nano-grating; Extraordinary optical transmission; waveguide; Electrical and Computer Engineering